2007
DOI: 10.1590/s1415-52732007000600002
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e práticas alimentares de trabalhadores acidentados

Abstract: OBJETIVO: Identificar o estado nutricional e as práticas alimentares de trabalhadores acidentados de Piracicaba, SP. MÉTODOS: Estudo transversal com 600 trabalhadores acidentados, atendidos em um dos 8 serviços especializados do município, entre maio e outubro de 2004. Foram caracterizados a situação socioeconômica, ocupacional, as práticas alimentares e o estado nutricional (peso, altura e circunferência de cintura), verificando médias e desvio-padrão. RESULTADOS: Os acidentados eram, fundamentalmente, homens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
1
1
3
Order By: Relevance
“…The percentage of breakfast skipping in the sample studied was lower than that in other Brazilian studies [21,36,37]. The study in [36] that evaluated Brazilian adults ( n = 600) found that 24% skipped breakfast. Marchioni et al [21] evaluated 795 adolescents in São Paulo/Brazil and found that 38% skipped breakfast.…”
Section: Discussioncontrasting
confidence: 55%
“…The percentage of breakfast skipping in the sample studied was lower than that in other Brazilian studies [21,36,37]. The study in [36] that evaluated Brazilian adults ( n = 600) found that 24% skipped breakfast. Marchioni et al [21] evaluated 795 adolescents in São Paulo/Brazil and found that 38% skipped breakfast.…”
Section: Discussioncontrasting
confidence: 55%
“…A ingestão adequada desses grupos de alimentos acarreta diversos benefícios ao organismo, pois são excelentes fontes de fibras, minerais, vitaminas e outros compostos que auxiliam na prevenção e controle de doenças 37,24 . Estudos também apontam que os trabalhadores em geral não incorporam esses alimentos à rotina 38,39 . Ainda, segundo a Pesquisa de Orçamentos Familiares (POF) de 2017/2018, a aquisição de frutas e hortaliças está abaixo da recomendação da organização mundial da saúde nas cinco regiões brasileiras e em todas as classes de rendimento 40 .…”
Section: Resultsunclassified
“…The abovementioned growth is confirmed by the increasing prevalence of overweight and obesity and related comorbidities in workers 43,44 . Another aspect deserving of attention is work-and environment-related diseases, which would also benefit from dietitians' skillful care 43,44 . The Programa Nacional de Alimentação Escolar (PNAE, National School Food Program) also promoted a great demand for dietitians in the educational sector.…”
Section: Demands and Challenges For Educating Dietitians In Today's Wmentioning
confidence: 88%